Worker mobility under attack? Explaining labour market chauvinism in the EU. Issue 10 (3rd October 2018) - Ferrera, Maurizio; Pellegata, Alessandro
ABSTRACT: The aim of this paper is to investigate citizen views on the free movement of workers within the European Union (EU). We are interested in how situational and relational factors affect labour market chauvinist attitudes. Drawing on the threat theory, we advance new hypotheses on the role of intertemporal relative deprivation in amplifying chauvinist inclinations. From the intergroup contact theory and transnational approaches, we borrow insights on the role played by cross-border experiences and inclusion in discursive and associational networks in containing chauvinism. The analysis uses the original 'Reconciling Economic and Social Europe' (REScEU) survey conducted in six EU countries (i.e., France, Germany, Italy, Poland, Spain and Sweden) in the fall of 2016. The article shows that – though rooted in class and status positions – chauvinist attitudes are clearly sensitive to contingent situations and lifeworld experiences.